Prospective observational non-randomized trial protocol for surgical planner 3D image processing & reconstruction for locally advanced colon cancer - Jerí-McFarlane, Sebastián; García-Granero, Álvaro; Pellino, Gianluca; Torres-Marí, Noemi; Ochogavía-Seguí, Aina; Rodríguez-Velázquez, Miguel; Gamundí-Cuesta, Margarita; González-Argenté, Francisco Xavier (BMC surgery, 2024)
Introduction Colon cancer presents significant surgical challenges that necessitate the development of precise strategies. Standardization with complete mesocolic excision (CME) is common, but some cases require extended resections. This study investigates the use of 3D Image Processing and Reconstruction (3D-IPR) to improve diagnostic accuracy in locally advanced colon cancer (LACC) with suspected infiltration and achieve R0 surgery. Methods Single-center, prospective, observational, comparative, non-randomized study. • Participants : Patients aged > 18 years undergoing LACC surgery, as indicated by CT scans, confirmed via colonoscopy. Exclusion criteria include neoadjuvant therapy, suspected carcinomatosis on CT, and unresectable tumors. • Interventions : 3D-IPR models are used for surgical planning, providing detailed tumor and surrounding structure metrics. Surgical procedures are guided by CT scans and intraoperative findings, categorized by surgical margins as R0, R1, or R2. • Objective : The primary goal is to evaluate 3D-IPR’s utility in achieving R0 resection in LACC with suspected infiltration. Secondary objectives include assessing preoperative surgical strategy, comparing CT reports, detecting adenopathy, and identifying vascularization and anatomical variants. • Outcome : The main outcome is the diagnostic accuracy of 3D-IPR in determining tumor infiltration of neighboring structures compared to conventional CT scans, using definitive pathological reports as the gold standard. Results • Recruitment and Number Analyzed : The study aims to recruit about 20 patients annually over two years, focusing on preoperative 3D-IPR analysis and subsequent surgical procedures. • Outcome Parameters: These include loco-regional and distant recurrence rates, peritoneal carcinomatosis, disease-free and overall survival, and mortality due to oncologic progression. • Harms : No additional risks from CT scans, as they are mandatory for staging colon tumors. 3D-IPR is derived from these CT scans. Discussion If successful, this study could provide an objective tool for precise tumor extension delimitation, aiding decision-making for radiologists, surgeons, and multidisciplinary teams. Enhanced staging through 3D-IPR may influence therapeutic strategies, reduce postsurgical complications, and improve the quality of life of patients with LACC. Trial registration Trial is registered at ISRCTN registry as ISRCTN81005215. Protocol version I (Date 29/06/2023).